Family Instability and Children's Health. Issue 4 (10th November 2017) - Smith, Chelsea; Crosnoe, Robert; Cavanagh, Shannon E.
Abstract : Research on family instability is fertile ground for translation into policy and practice. This article describes how basic science in this area can more effectively support work in later stages of the translational research process. To begin, the scope of family instability is outlined with trends, causes, and effects. Next, a conceptual model of the effects of family instability on children's health identifies focal aspects that could be leveraged for translational research: developmental domain, developmental time, mechanisms, and points of variation. The guidelines presented are meant to be general and applicable to a variety of topics and fields in which family scholars aim to improve basic research that can contribute to and move forward a translational family science.